Kalanchoe thrysiflora Harv. and Kalanchoe marmorata Baker, DNA Profiling, biological guided fractionation of different extracts, isolation and identification of cytotoxic compounds - Abdel Nasser Singab, Sherweit El-Ahmady, Rola Milad, Sally Saad (Journal of Applied Pharmaceutical Science)
DNA profiling of two closely related ornamental plants belonging to family crassulaceae viz. Kalanchoe thrysiflora Harv. and Kalanchoe marmorata Baker were performed to establish genetic polymorphism. Biological guided fractionation of the two plant extracts to assess their cytotoxicity, had led to the isolation of one steroidal and one triterpenoidal compound from the most active dichloromethane fraction of Kalanchoe thrysiflora. The cytotoxicity of the isolated compounds were evaluated against normal (HFB4) and cancer (MCF7) cells. Compound 1 (3-oxo-olean-12-ene) and compound 2 (β-sitosterol) showed similar cytotoxic activity on MCF7 at IC50 17.4 and 17.6 µg/ml respectively while on HFB4, the compounds revealed cytotoxic activity at IC50 21.9 and 21.6 respectively.
Keywords: Crassulaceae,cytotoxicity,DNA profiling,Kalanchoe thrysiflora,Kalanchoe marmorata.